H∞ control for a class of discrete-time singular systems via dynamic feedback controller. (August 2016) - Long, Shaohua; Zhong, Shouming
Abstract: This paper deals with the H ∞ control problem for a class of discrete-time singular systems. A dynamic feedback control scheme is considered in this paper, while few results in the existing literature employed it to study the H ∞ control problem for the discrete-time singular systems. By using the Lyapunov functional method and the linear matrix inequality (LMI) approach, a sufficient condition for the existence of a dynamic feedback controller that guarantees the resulting closed-loop system to be admissible with given H ∞ performance index is derived. Finally, a numerical example is provided to show the effectiveness of the proposed method.